Post-traumatic stress disorder and related factors in students whose school burned down: Cohort study - Chawanun Charnsil (2020)
© 2020 Elsevier B.V. Aims: This research examines the prevalence of post-traumatic stress disorder (PTSD) and its related factors in students whose school burned down, one month and six months after the incident. Methods: A total of 56 students from grades one through six were invited to participate in this study with permission from their parents. Subjects were screened for PTSD by using UCLA PTSD Reaction Index (DSM-5 Version) during three periods: 1, 6, and 12 months after the incident. Children diagnosed with PTSD were interviewed by a child and adolescent psychiatrist to confirm their diagnosis and obtain related factors. Percentage and logistic regression were used for statistical evaluation. 5 out of the 56 students (8.9 %) had PTSD one month after the incident, 2 of them recovered after six months. 6 out of 56 students (10.7 %) had PTSD at six months and 2 of 40 (5%) had PTSD at one year after the incident. Students who lived in the school's dorms had significantly more PTSD than those who lived elsewhere, p < 0.01, RR = 5.16 (4.04–6.6). After one year, age was the only factor related to PTSD (p = 0.01, odds ratio = 0.452). Conclusion: Post-traumatic stress disorder is a common disorder in children after a disaster. Although some can recover shortly after an incident, others develop symptoms one month after the incident. Age is a risk factor that can lead to the development of PTSD.